Pengaruh Net Working Capital, Debt to Equity Ratio, Total Assets Turn Over, Dan Intellectual Capital Pada Kinerja Perusahaan - Handayani, Herlina; Fachruddin Arrozi, Muhammad (CV. Lafadz Jaya, 2023)
Technological developments have an impact on Firm performance, particularly in the food and beverage sector. Because of this, this study aims for companies to pay attention to company liquidity, risk management, asset management, and human resource management to maintain a competitive position and maintain strong Firm performance. TCausesearch design is a causality design (cause and effect). By using the Hypothetico-Deductive method, which aims to provide an overview of what will affect the Firm's performance to keep growing and stable, and to test the hypotheses that have been formulated by researchers. There are 84 Food and Beverage companies that have been registered with the IDX in 2022. The sample was taken using a purposive sampling method, where the sample was obtained using a number of considerations and certain criteria. The results of this study indicate that Net working capital (NWC) has a positive and significant influence on Return On Investment (ROI), Debt to Equty Ratio (DER) has a negative and significant influence on Return On Investment (ROI), Total Assets Turnover (TATO). has a positive and significant influence on Return On Investment (ROI), Intellectual Capital (IC) has a positive and significant influence on Return On Investment (ROI). The findings of this study can help companies adapt to changing market conditions and improve their performance in facing globalization.